Seeing emotions without mindreading them - Smortchkova, J (Springer Verlag, 2016)
According to direct perception approaches we directly see others’ emotions, and by seeing emotions we immediately ascribe them to others. Direct perception is explicitly presented as an alternative account of mindreading (the ability to recognize and attribute mental states to others), but it also contains an implicit thesis about the extent of the reach of perception. In this paper emotion perception is defended: siding with the direct perception approach I claim that we can simply see emotions and not just low level features of the facial and bodily displays, but contra the direct perception approach I argue that seeing emotions is not sufficient for recognizing emotions as mental states in order to ascribe them to others.